Peran Mahasiswa Ekonomi Islam dalam Meningkatkan Tata Kelola dan Transparansi di Kantor Camat Guguak Panjang Kota Bukittinggi - Aziza Nabela (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This study discusses the role of Islamic Economics students in supporting the improvement of governance and transparency at the Guguak Panjang Sub-District Office, Bukittinggi City. Students undertaking internships had the opportunity to contribute directly to administrative processes and public services within the sub-district office. The focus of the activities was directed toward introducing Islamic economic principles such as amanah (responsibility), honesty, and openness in administrative management practices and simple financial recording. The methods used included observation and mentoring in the daily work activities of the sub-district staff. The results showed that the presence of students had a positive impact in assisting staff to improve discipline in record-keeping, enhance documentation systems, and raise awareness of the importance of transparency in public services. Thus, the role of Islamic Economics students not only provided them with practical experience but also added value to government institutions through the application of Sharia-based work ethics that can strengthen governance and improve public service quality.